Soil Inversion with Subsoiling Increases Cotton Yield Through Improving Soil Properties and Root Growth - Pengcheng Li; Shulin Wang; Weina Feng; Helin Dong; Cangsong Zheng; Miao Sun; Jingjing Shao; Zhenggui Zhang; Zhanlei Pan; Jian Wang; Guilan Sun; Junhong Li; et al. (Agronomy)
Long-termrotary tillage has led to a deterioration in cotton production. It remains unclear whether soil inversion with subsoiling could halt the deterioration. Here, a field experiment was set from 2015 to 2017 with three treatments: CK, 15 cm rotary tillage; T1, replace the top 20 cm soil layer with the 20–40 cm soil layer and loosen the 40–55 cm soil layer; T2, replace the top 20 cm soil layer with the 20–40 cm soil layer and loosen the 40–70 cm soil layer. The results showed that the total nitrogen(N) content, alkaline N content, total phosphorous(P) content, available P content, and available potassium(K) content of T1 and T2 in the 20–40 cm soil layer were significantly higher than those in the top 20 cm soil layer in 2017, and the soil nutrient contents in the top 20 cm soil layer increased with each planting season. Compared with CK, the root dry matter of T1 and T2 increased by 13.1% and 15.2%, respectively, and the boll number and boll weight were also significantly higher, and the seed cotton yield under T1 for the three years increased by 7.7%, 7.6%, and 6.1%, respectively, and the seed cotton yield under T2 for the three years increased by 6.1%, 8.6%, and 8.2%, respectively. The results suggest that soil inversion with subsoiling is a continuously effective tillage practice for increasing the output of cotton in the North China Plain.